Atomic Modulation and Structure Design of Carbons for Bifunctional Electrocatalysis in Metal–Air Batteries. Issue 13 (24th September 2018) - Huang, Yiyin; Wang, Yueqing; Tang, Cheng; Wang, Jun; Zhang, Qiang; Wang, Yaobing; Zhang, Jintao
Abstract: With the extensive research and development of renewable energy technologies, there is an increasing interest in developing metal‐free carbons as a new class of bifunctional electrocatalysts for boosting the performance of metal–air batteries. Along with significant understanding of the electrocatalytic nature and the rapid development of techniques, the activities of carbon electrocatalysts are well‐tailored by introducing particular dopants/defects and structure regulation. Herein, the recent advances regarding the rational design of carbon‐based electrocatalysts for the oxygen reduction reaction and oxygen evolution reaction are summarized, with a special focus on the bifunctional applications in Zn–air and Li–air batteries. Specifically, the atomic modulation strategies to regulate the electrocatalytic activities of carbons and structure modification are summarized to gain deep insights into bifunctional mechanisms and boost advanced Zn–air and Li–air batteries. The current challenges and future perspectives are also addressed to accelerate the exploration of promising bifunctional carbon catalysts for renewable energy technologies, particularly metal–air batteries. Abstract : Recent advances regarding the rational design of carbon‐based electrocatalysts via atomic modulation and structure modification for the oxygen reduction and evolution reactions are summarized, with a special focus on their bifunctional applications in Zn–air and Li–air batteries.